Culpeper's complete herbal - Culpeper, Nicholas, 1616-1654 (Sterling Publishing Company, 2019)
The classic book on herbal remedies, newly illustrated, edited and with commentary by US herbalist and author Steven Foster. It combines the charm and information of Culpeper's original seventeenth-century text with up-to-date, modern, practical usage. It includes details about where to find each herb, astrology, and medicinal benefits. -- adapted from publisher's web site.